Pergeseran Budaya Kerja di Timur Tengah pada Era Remote Work dan Gig Economy - Pauly Demanda (PT. Saha Kreasi Indonesia, 2025)
The shift in work culture in the Middle East, driven by the rise of remote work and the gig economy, has brought significant challenges and opportunities. This study explores how these two phenomena interact with the region's existing social and cultural structures, and how they impact work patterns, productivity, and workers' well-being. Countries such as the UAE, Qatar, and Saudi Arabia have embraced technology to diversify their economies, previously reliant on energy sectors, and are now seeing increasing adoption of digital work models. The study provides insights into how these changes shape the labor market, government policies, and the future of work in the Middle East. By understanding these shifts, the research contributes to knowledge on how cultures and economies adapt to the digitalization of labor and the evolving global work environment. The findings highlight the need for educational reforms and government policies to support digital literacy, ensure social protection, and address inequalities in the emerging digital workforce.